2020
DOI: 10.1080/02688697.2020.1861433
|View full text |Cite
|
Sign up to set email alerts
|

SARS coronavirus 2 and central nervous system manifestations: causation, relation, or coexistence? a case series study and literature review

Abstract: Introduction: Recently, weeks after the COVID-19 prevalence, there were reports of brain involvement and neurologic presentations in the COVID-19. Case presentation: We present five cases of COVID-19 and cerebrovascular events. A 34-year-old woman with IVH and ischemic stroke. A 60-year-old man with multiple small hemorrhagic foci and mild IVH in the occipital horn. A 63-year-old woman with large left parietooccipital intracerebral hemorrhage (ICH) and IVH. A 56-year-old man with left hemispheric and midbrain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Despite being initially described as a respiratory disease, in the course of time it was observed that other organs and systems could be affected by COVID-19, such as cardiovascular system ( 5 ), central nervous system ( 6 ), kidney ( 7 ), liver ( 8 ), among others. Endocrine system is also affected by COVID-19, including pancreas, adrenal, testicle, reproductive tract, parathyroid gland and the thyroid gland ( 9 14 ) ( Figure 1 ).…”
Section: Covid-19 and Thyroid Gland: General Conceptsmentioning
confidence: 99%
“…Despite being initially described as a respiratory disease, in the course of time it was observed that other organs and systems could be affected by COVID-19, such as cardiovascular system ( 5 ), central nervous system ( 6 ), kidney ( 7 ), liver ( 8 ), among others. Endocrine system is also affected by COVID-19, including pancreas, adrenal, testicle, reproductive tract, parathyroid gland and the thyroid gland ( 9 14 ) ( Figure 1 ).…”
Section: Covid-19 and Thyroid Gland: General Conceptsmentioning
confidence: 99%
“…The extent of CNS involvement can be influenced by various factors such as genetic predisposition, comorbidities, and environmental factors, which can increase COVID-19 patient's risk of adverse outcomes. Coronaviruses have been shown to invade vascular endothelial cells, which allows the viral particles to directly access CNS neural and glial cells, resulting in a myriad of pathological cerebrovascular changes [ 3 , 4 , 5 , 6 , 7 ]. A case series study by Mao et al [ 8 ] showed that patients who developed severe COVID-19 infection according to their respiratory status had neurologic manifestations, such as acute cerebrovascular diseases (CVDs).…”
Section: Introductionmentioning
confidence: 99%